1998
DOI: 10.31899/pgy6.1018
|View full text |Cite
|
Sign up to set email alerts
|

Women's lives and rapid fertility decline: Some lessons from Bangladesh and Egypt

Abstract: In some of the more traditional parts of the world, fertility is falling steadily, sometimes rapidly, in environments where women's lives remain severely constrained. The recent experiences of Bangladesh and Egypt, both predominantly Muslim countries, are illustrative in this regard. Since the late 1970s, rural and urban areas in both countries have experienced steady declines in fertility, with recent declines in rural Bangladesh similar to those in rural Egypt, despite lower levels of development and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Obermeyer rejects the view that there is any necessary connection between Islam and women's autonomy. Moreover, recent empirical studies have found no evidence that Muslim women have less autonomy than women belonging to other religious groups in the same societies (Jejeebhoy and Sathar 2001;Morgan et al 2002), and have questioned the link between autonomy and fertility in these populations (Amin and Lloyd 2002;Morgan et al 2002). For our purposes, the debate on reli-gion, women's autonomy, and fertility supports several conclusions.…”
Section: The Sources Of Religious Influence Religion and Valuesmentioning
confidence: 66%
“…Obermeyer rejects the view that there is any necessary connection between Islam and women's autonomy. Moreover, recent empirical studies have found no evidence that Muslim women have less autonomy than women belonging to other religious groups in the same societies (Jejeebhoy and Sathar 2001;Morgan et al 2002), and have questioned the link between autonomy and fertility in these populations (Amin and Lloyd 2002;Morgan et al 2002). For our purposes, the debate on reli-gion, women's autonomy, and fertility supports several conclusions.…”
Section: The Sources Of Religious Influence Religion and Valuesmentioning
confidence: 66%
“…Goldin and Katz () argue that family planning and fertility decline mean that women could enter the labor force and avail themselves of the opportunity to get long‐ term education and pursue careers typically reserved for men. Amin and Lloyd () argue that fertility declines appear to have empowered women by increasing their access to and control of resources, noting that increased school enrollment for girls, more access to credit, new ideas about reproductive control, and increased social networks as the key aspects of improved life options for women (see also Malhotra, ). Also, as Sajid () had argued, population growth adversely affects gender equality in education.…”
Section: Brief Review Of the Literaturementioning
confidence: 99%
“…Gender relations and gender value systems have long been conceptualized as major determinants of attitudes concerning fertility, although empirical evidence suggests that their impact depends partly on other contextual factors (McDonald 2000;Kravdal 2001;Mason 2001;Morgan et al 2002;Amin and Lloyd 2002). Our framework specifies that gender stratification has a direct effect on both the perception of the costs and benefits of having children and on the costs of fertility regulation.…”
Section: Determinants Of Replacement Fertility: the "Apa" Analytical mentioning
confidence: 99%